The role of pathogen-mediated insect superabundance in the East African emergence of a plant virus - Ruairí, Donnelly; Christopher A, Gilligan (John Wiley & Sons, Ltd, 2022)
Abstract 1. One of the major crops for food security is cassava. Superabundant Bemisia tabaci whitefly, comprising unusually high landscape populations of the insect, have been implicated in cassava virus emergence. Studies have been unable to select from several hypotheses, however, as to the dynamic drivers of superabundant whitefly associated with the emergence in East Africa of severe cassava mosaic disease. One possibility is that pathogenic modification of infected plants can itself increase the growth of insect vector colonies on infected plants. 2. Through the modelling of population processes at the landscape scale we introduce a framework for analysing patterns in the association of disease and insect waves. 3. Our analyses demonstrate the role of pathogen-mediated insect superabundance in a plant disease invasion. 4. Synthesis. An elevated abundance of insects at the landscape scale is frequently implicated in invasions of the plant pathogens that they carry. We advance ecological understanding of plant disease invasions by showing how landscape data can be used to investigate the causes of insect vector superabundance.
Keywords: invasion, manipulation, vector, superabundance, plant pathogen